2023
DOI: 10.1055/a-2180-9872
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of persistent SARS-CoV-2 gut infection in patients with a history of COVID-19: Insights from endoscopic examination

Mohamed Hany,
Eman Sheta,
Ahmed Talha
et al.

Abstract: Background: Gut affection is common during acute COVID-19, and persistent SARS-CoV-2 gut infection has been reported months after the initial infection, potentially linked to long COVID syndrome. This study tested the incidence of persistent gut infection in patients with a history of COVID-19 undergoing endoscopic examination. Methods: Endoscopic biopsies were prospectively collected from patients with previous COVID-19 infection undergoing upper or lower gastrointestinal endoscopy (UGE or LGE). Immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Lapa et al reported that in patients who survived and recovered after SARS-CoV-2 infection, hair loss, obesity, memory loss and hypercholesterolemia were observed 3-6 months later, in the period they named as "Post-covid Syndrome" [38]. A recent study conducted by Hany et al showed that virus particles SARS-CoV-2 form long-term viral reservoirs in the gastrointestinal tract mucosa [39]. The potential for SARS-CoV-2 to create a long-term reservoir and cause damage in the gastrointestinal (GI) mucosa, coupled with one of the entry routes of SARS-CoV-2 being the oral cavity, suggests the possibility of long-term infection in the oral region.…”
Section: Discussionmentioning
confidence: 99%
“…Lapa et al reported that in patients who survived and recovered after SARS-CoV-2 infection, hair loss, obesity, memory loss and hypercholesterolemia were observed 3-6 months later, in the period they named as "Post-covid Syndrome" [38]. A recent study conducted by Hany et al showed that virus particles SARS-CoV-2 form long-term viral reservoirs in the gastrointestinal tract mucosa [39]. The potential for SARS-CoV-2 to create a long-term reservoir and cause damage in the gastrointestinal (GI) mucosa, coupled with one of the entry routes of SARS-CoV-2 being the oral cavity, suggests the possibility of long-term infection in the oral region.…”
Section: Discussionmentioning
confidence: 99%
“…At autopsy, SARS-CoV-2 RNA was found throughout the body, including brain tissue, for up to 230 days after onset of symptoms. Hany et al [28] recently reported that SARS-CoV-2 can form long-term viral reservoirs in the GI tract’s mucosa.…”
Section: Etiology Of Long Covidmentioning
confidence: 99%